The Pauline effect: the use of the Pauline epistles by early Christian writers - Strawbridge, Jennifer R. (Studies of the Bible and its reception, 2015)
This study offers a fresh approach to reception historical studies of Scripture, utilizing a methodology introduced by scholars of ancient history and focusing on the four most frequently used Pauline pericopes in pre-Nicene writings. Engaging a wide range of primary texts, it traces the contours and overlap between theology and interpretation of Scripture and examines how these particular texts formed early Christians and their writings